Determination of borax content in wet noodles circulating in market by uv-vis spectrophotometry method using curcumin reagent - Raisani Rusli (International Journal of Nursing and Midwifery Research, 2022)
The determination of borax contains in wet noodles done by curcumin reagent as color regent which produced rosocyanin complexes and monitor by using UV-Vis spectrophotometry in maximum wave length at 545.95 nm. Before it was used in a sample which was taken from Ciputat market, this method was validated. The results showed that calibration curve in linear 6.25-50 µg/ml with regression equal y = 0.008 + 0.012x and correlation coefficient (r) = 0.9994. this method gave detection limit at 3.1132 µg/ml and qualification limit at 10.3775 µg/ml. The simulation recovery of wet nodles was 99.767 ± 1.114 %. The result of examination of wet noodles sample which was marketed in Ciputat market that four of five contained 3.76112 ± 0.0451, 108.592 ± 0.02185, 117.9461 ± 0.01455, and 6.275 ± 0.0221 borax.